Malaysian finance sector weak-form efficiency: Heterogeneity, structural breaks, and cross-sectional dependence - Sook Ching Kok; Qaiser Munir (Journal of Economics, Finance and Administrative Science, 2015)
This study examines the weak-form efficient market hypothesis (EMH) for the Finance Sector in Malaysian Stock Exchange, by exploring and scrutinizing the firm-level efficiency over for the period from 1st January 1997 to 31st December 2014. For this purpose, we apply panel nonlinear unit root test that accounts for heterogeneity, and panel stationarity test to allow for the presence of structural breaks and cross-sectional dependence (CSD). The main findings of this study suggest the following: first, there is a strong CSD among the price series of finance stocks; second, unlike the traditional panel unit root tests that provide mixed-results, the panel stationarity test which incorporates structural breaks and CSD suggests that these series are characterized as random walk processes implying the Finance Sector is weak-form efficient. The finding of weak-form efficiency has salient implications in terms of capital allocation, stock price predictability, forecasting technique, and the impact of shocks to stock prices. – – Este estudio examina la forma débil de la hipótesis de los mercados eficientes (EMH) para el sector financiero de la Bolsa de Malasia, explorando y examinando la eficiencia a nivel empresarial durante el período transcurrido entre el 1 de enero de 1997 y el 31 de diciembre de 2014. A tal fin, aplicamos un test de raíz unitaria no lineal del panel para justificar la heterogeneidad, y un test de estacionalidad del panel para permitir la presencia de brechas estructurales y de dependencia transversal (CSD). Los principales hallazgos de este estudio sugieren lo siguiente: en primer lugar, existe una sólida dependencia transversal entre las series de precios de los valores financieros; en segundo lugar, a diferencia de los test tradicionales de raíz unitaria que aportan resultados mixtos, el test de estacionalidad del panel, que incorpora brechas estructurales y dependencia transversal, refleja que dichas series están caracterizadas por procesos de recorrido aleatorio que implican la forma débil de la eficiencia del sector financiero. El hallazgo de la forma débil de la eficiencia contiene implicaciones destacadas en términos de distribución del capital, previsibilidad de los precios de los valores, técnica de previsiones e impacto de las perturbaciones sobre los precios de las acciones.
Keywords: G14; 330; Market efficiency; Financial firms; Banks; Heterogeneity; Panel data; Structural breaks; Cross-sectional dependence; Eficiencia del mercado; Entidades financieras; Bancos; Heterogeneidad; Datos del panel; Brechas estructurales; Dependencia transversal